2002
DOI: 10.1002/1521-3757(20020703)114:13<2514::aid-ange2514>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Chirality and Macroscopic Polar Order in a Ferroelectric Smectic Liquid-Crystalline Phase Formed by Achiral Polyphilic Bent-Core Molecules

Abstract: Materials with a macroscopic polar order have a variety of useful properties, such as piezo-and pyroelectricity and second-order nonlinear optical activity [1, 2] Especially ferroelectric (FE) and antiferroelectric (AF) liquid crystalline (LC) materials are of great interest, because they can be rapidly switched between different states by means of external electrical fields. [3, 4] These properties makes them useful for numerous applications, such as electrooptic devices, information storage, switchable NLO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 28 publications
1
60
1
4
Order By: Relevance
“…One of them is that under polarizing microscope, we see no chiral domains of opposite handedness in the ground state of the DC phase. As we discussed, the DC phase consists of SmCP structure with short range interlayer correlation length [10][11][12][13][14][15][16][17][18][19]. The absence of opposite handed domains in our sample indicates two possibilities for the ground state arrangement of the layers: The adjacent layers are either homochiral (SmC s P S or SmC a P A type), making the overall structure chiral, though the opposite handed domains are smaller than the wavelength of the visible light.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of them is that under polarizing microscope, we see no chiral domains of opposite handedness in the ground state of the DC phase. As we discussed, the DC phase consists of SmCP structure with short range interlayer correlation length [10][11][12][13][14][15][16][17][18][19]. The absence of opposite handed domains in our sample indicates two possibilities for the ground state arrangement of the layers: The adjacent layers are either homochiral (SmC s P S or SmC a P A type), making the overall structure chiral, though the opposite handed domains are smaller than the wavelength of the visible light.…”
Section: Discussionmentioning
confidence: 99%
“…During this process a simultaneous reversal in the polarization and the tilt direction takes place giving rise to a switching from SmC s P A to SmC a P S and SmC a P A to SmC s P S . Bent-core mesogens are well known for the optically isotropic phases they exhibit, which include the B4 phase [7][8][9], the dark conglomerate (DC) [10][11][12][13][14][15][16][17][18][19] and the dark enantiomeric (DE) phases [20]. The DC phase, which is the topic of interest of this paper, is usually found to occur below the isotropic phase.…”
Section: Introductionmentioning
confidence: 99%
“…The in-layer frustration caused by orthogonal tilting of the molecular segments can be relieved by the saddle-splay curvature: in three dimensions, the DC phases have significant negative Gaussian curvature. Depending on the local structure, the DC phases are classified as liquid crystalline sponge-like phases [28][29][30][31][32][33][34][35][36][37] and Helical Nano-Filament (HNF) phases or B4 phases [38][39][40]. In addition to these, a number of DC phases with intermediate or distinct nanostructures have been observed [41][42][43][44][45][46][47][48].…”
Section: Dark Conglomerate Phasesmentioning
confidence: 99%
“…Incorporation of a perfluorinated chain segment or silicon-containing unit (e.g., siloxane and carbosilane) into the hydrocarbon chain as an end group is useful to modulate mesophase properties. It was reported that mesophase stabilization was observed for bent-core molecules including two partially perfluorinated tails [36,94], and bent-core molecules incorporating nanosegregated siloxane end groups into one or two tails display a transformation from AF to FE switching [95].…”
Section: General Molecular Structure Of Bent-core Lcsmentioning
confidence: 99%
“…The Tschierske group reported that incorporation of terminal siloxane units at one tail of bent-core molecules leads to a transition from AF to FE switching [95]. A large number of such molecules including siloxane and carbosilane units were subsequently reported [134][135][136][137][138][139][140][141][142][143][144][145][146][147], and many of them exhibit DC phases with surface-stabilized bistable FE switching.…”
Section: Tilted Polar Smectic (Smcp) Phasesmentioning
confidence: 99%